Changes in the D region associated with three recent solar eclipses in the South Pacific region - Kumar, Sushil; Kumar, Abhikesh; Maurya, A.K.; Singh, Rajesh (My University, 2016)
We estimate D region changes due to 22 July 2009 total solar eclipse (SE), 13–14 November 2012 total SE, and 9–10 May 2013 annular SE, using VLF navigational transmitters signal observations at Suva, Fiji. The North West Cape (NWC) signal (19.8 kHz) showed an amplitude and phase decrease of 0.70 dB and 23° during November SE and 2.0 dB and 90° duringMay SE. Themodeling using Long Wave Propagation Capability code for NWC-Suva path during November and May SEs showed an increase in average D region reflection height (H′) and sharpness factor (β) by 0.6 and 0.5 km and 0.012 and 0.015km 1, respectively. The July total SE for JJI-Suva path showed an increase in H′ of 1.5 km and a decrease in β of 0.055 km 1. The decrease in the electron density calculated using SE time H′ and β is maximum for July total SE and minimum for May annular SE. The effective recombination coefficient estimated from the decay and recovery of signal phase associated with May annular SE was higher (27%) than normal daytime value 5.0 × 10 7cm 3 s 1 and varied between 1.47 × 10 6 and 1.15 × 10 7cm 3 s 1 in the altitude 70 to 80 km. Morlet wavelet analysis of signals amplitude shows strong wave-like signatures (WLS) associated with three SEs with period ranging 24–66 min, but the intensity and duration of WLS show no clear dependence on SE magnitude and type. Apart from the cooling spot, the eclipse shadow can also generate WLS associated with atmospheric gravity waves.
Keywords: Solar eclipse; South Pacific region